Carbon-Containing Polymer Composites - Rahaman, Mostafizur; Khastgir, Dipak; Aldalbahi, Ali Kanakhir (Springer Series on Polymer and Composite Materials, 2019)
This book discusses the methods synthesizing various carbon materials, like graphite, carbon blacks, carbon fibers, carbon nanotubes, and graphene. It also details different functionalization and modification processes used to improve the properties of these materials and composites. From a geometrical-structural point of view, it examines different properties of the composites, such as mechanical, electrical, dielectric, thermal, rheological, morphological, spectroscopic, electronic, optical, and toxic, and describes the effects of carbon types and their geometrical structure on the properties and applications of composites.